FOSTERING AN INCLUSIVE ATTITUDE AS A FUNDAMENTAL PRINCIPLE OF CULTURAL LITERACY THROUGH THE STUDY VISIT METHOD AT SD NEGERI 7 MANGGAR (PIONIR: JURNAL PENDIDIKAN, 2025)
This research is motivated by the phenomenon of diminishing appreciation among students with different cultural backgrounds. The research was conducted at SD Negeri 7 Manggar, East Belitung Regency. In this study, the researcher intends to review the application of the study visit method as an effort that has been undertaken by school to support the process of cultural literacy, which then serves as a response to the existing phenomenon. A qualitative approach is used in this research because it allows for a more accurate understanding of the phenomena that occur. The method used is narrative inquiry research, this method was chosen because it relates to experiences and life events. The research process is supported by using observation and unstructured interview data collection techniques. The data used was then analyzed with reference to the data analysis by Miles, Huberman, and Saldana. The research findings explain that through the process of cultural literacy by conducting study visits to traditional houses in Belitung, teachers can guide students' understanding of local cultural values, particularly the values of mutual respect and cooperation embodied in the traditional houses of Belitung. These cultural values then contribute to fostering an inclusive attitude among students in their daily lives and serve as a unifying strength amidst the cultural diversity in Indonesia.